The microbiome in asthma. Issue 6 (December 2016) - Noval Rivas, Magali; Crother, Timothy R.; Arditi, Moshe
Abstract : Purpose of review: Asthma is a complex and heterogeneous disease with strong genetic and environmental components that manifests within a variety of clinical features and diverse patterns of immune responses. Asthma prevalence has dramatically increased over the last decade in Westernized societies, thereby suggesting a key function of environmental factors in disease promotion and development. Recent findings: 'Early-life' microbial exposure and bacterial colonization are crucial for the maturation and the education of the immune system. The commensal flora is also critical in order to maintain immune homeostasis at the mucosal surfaces and may consequently play an important function in allergic disease development. Recent evidence demonstrates that asthma influences and is also impacted by the composition and function of the human intestinal and respiratory microbiome. Summary: In this review, we summarize the most recent findings on how asthma development is connected with respiratory and intestinal microbial dysbiosis. We highlight and discuss recent research that reveals the existence of a 'gut–lung' microbial axis and its impact on asthma development. We also analyze how 'early-life' microbial exposure affects the immune response and the consequences for asthma development.